2022
DOI: 10.1186/s13018-022-02980-2
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic-loaded calcium sulfate in clinical treatment of chronic osteomyelitis: a systematic review and meta-analysis

Abstract: Background Present work was aimed to gather accessible evidence on the eradication rates and related postoperative complications of antibiotic-loaded calcium sulfate (CS) as an implant in the treatment of chronic osteomyelitis (COM). Methods Databases including PubMed, EMBASE, Medline, Ovid and Cochrane library were searched from their dates of initiation until November 2021. Two independent authors scrutinized the relevant studies based on the eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 48 publications
0
17
0
Order By: Relevance
“…Internal or external fixation, and autologous iliac crest bone grafting, was utilized when deemed necessary by the surgical team for the non-union cases (n = 16). view focuses on the subset of those patients with infected non-union and fracture-related infection, data concerning cases of osteomyelitis not directly related to fracture or nonunion are not extensively discussed here: information on the role of AICS in chronic osteomyelitis can be found in other systematic reviews on the topic (Shi et al, 2022;Thahir et al, 2022).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Internal or external fixation, and autologous iliac crest bone grafting, was utilized when deemed necessary by the surgical team for the non-union cases (n = 16). view focuses on the subset of those patients with infected non-union and fracture-related infection, data concerning cases of osteomyelitis not directly related to fracture or nonunion are not extensively discussed here: information on the role of AICS in chronic osteomyelitis can be found in other systematic reviews on the topic (Shi et al, 2022;Thahir et al, 2022).…”
Section: Resultsmentioning
confidence: 99%
“…Bone infections are notoriously difficult to treat due to the lack of antibiotic penetrance when delivered via the bloodstream (Lew and Waldvogel, 2004) Alternatively, antibiotics can be impregnated into bone cement and synthetic graft material, such as calcium sulfate and polymethyl methacrylate (PMMA), and be eluted over time at the site of infection (van Vugt et al, 2019;Shi et al, 2022). While systematic review articles by Thahir et al (2022) and Shi et al (2022) have recently been published reviewing the efficacy of antibioticimpregnated calcium sulfate (AICS) in treating osteomyelitis, there is no comprehensive review of the literature exploring its effects in treating infected non-union and fracture-related infection specifically (Shi et al, 2022;Thahir et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…In a vitro experiment, vancomycin and tobramycin impregnated materials had similar germicidal properties and elution efficiency [11]. Furthermore, a systematic review indicated that the choice of tobramycin-loaded CS or vancomycin combined with gentamicin-loaded CS did not affect the eradication rate and the incidence of postoperative complications in chronic osteomyelitis patients [13]. The choice of a local antibiotic depends on the local epidemiological data in patients who have no accurate bacterial data.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, calcium sulfate(CS) which can be impregnated with antibiotics, is osteoconductive and does not require a two stage procedure for removal; in addition, CS has been well characterized clinically as a bone void filler [9][10][11][12]. Tobramycin, vancomycin and gentamicin are common choices for CS loading [13]. Antibiotic-impregnated CS pellets have been applied in the treatment of pediatric HO and have been reported to yield satisfactory outcomes [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…No clinical studies have yet been published regarding the use of antibiotic-loaded bone composites for the treatment of AHOM. A systematic review and meta-analysis by Shi et al (2022) found 16 articles investigating the clinical treatment of chronic osteomyelitis with antibiotic-loaded calcium sulfate [9]. The authors found an eradication rate of 92% in the combined studies with no difference in the type of antibiotic used (tobramycin versus vancomycin combined with gentamycin).…”
Section: Discussionmentioning
confidence: 99%